O método Instrução por Colegas como estratégia didática na unidade de ensino potencialmente significativa : estudo de caso numa escola da rede pública - Lima, Évile Silva de (2020)
This research aimed to understand the Instruction by Colleagues method in the construction of learning from conceptual questions in a UEPS on the topic of Sunscreen for high school classes in the basic network and the students' conceptions about its implementation. It is understood that science teaching in the classroom fails to arouse the interest of students in view of the contents exposed in an expository (passive) way, as was seen in many pedagogical practices. Because the mere transmission of information does not make sense and does not prepare the student for life, therefore it is necessary to have a meaningful teaching and learning process. Given the above, among the various types of didactic sequence that have the potential to assist in the teaching and learning process, Potentially Significant Teaching Units (UEPS) were used, as the simple availability from situations developed in the sciences may instigate the curiosity, the criticality, the interest of the students, in addition to being able to be elaborated with other strategies, in this case, it was used together with the Instruction by Colleagues (IPC) method, as a teaching strategy within UEPS, whose theme worked was Sunscreen. So we tried to discuss a teaching and learning model that can meet society's desires, taking into account the student's prior knowledge, and that allows the school to (re) insert itself as the main promoter of the construction of knowledge, and may have a meaningful learning. The theoretical framework used was that of the Theory of Meaningful Learning and the methodology was of a qualitative nature, as for the objectives it is explanatory, and according to the research questions. The analysis methodology used was that of discursive textual analysis (ATD). The method used was Yin's case study, in a class of 17 high school students in basic education. The data analyzed were based on the previous questionnaire, the Conceptual Tests (TC) and finally, the final test, related to the students' conceptions regarding all activities developed. Based on the data analyzed, it can be concluded that the research provided us with promising results about the use of the Instruction by Colleagues method in potentially significant Teaching Units. The students responded satisfactorily to the adoption of the method and the interaction between them was important. It is worth mentioning that, the classroom experience with the method made us reflect on objects that should be cited: conceptual tests should be better chosen for greater interaction between students, the teacher must know the method properly before preparing the class. and its use and each step of the method must be used to the letter, as it has a specific function in the teaching and learning process.